Validating novel air pollution sensors to improve exposure estimates for epidemiological analyses and citizen science - Jerrett,M; Donaire-Gonzalez,D; Popoola,O; Jones,R; Cohen,RC; Almanza,E; de,Nazelle A; Mead,I; Carrasco-Turigas,G; Cole-Hunter,T; Triguero-Mas,M; Seto,E; et al. (Environmental Research, 2017)
Low cost, personal air pollution sensors may reduce exposure measurement errors in epidemiological investigations and contribute to citizen science initiatives. Here we assess the validity of a low cost personal air pollution sensor. Study participants were drawn from two ongoing epidemiological projects in Barcelona, Spain. Participants repeatedly wore the pollution sensor − which measured carbon monoxide (CO), nitric oxide (NO), and nitrogen dioxide (NO2). We also compared personal sensor measurements to those from more expensive instruments. Our personal sensors had moderate to high correlations with government monitors with averaging times of 1-h and 30-min epochs (r ~ 0.38–0.8) for NO and CO, but had low to moderate correlations with NO2 (~0.04–0.67). Correlations between the personal sensors and more expensive research instruments were higher than with the government monitors. The sensors were able to detect high and low air pollution levels in agreement with expectations (e.g., high levels on or near busy roadways and lower levels in background residential areas and parks). Our findings suggest that the low cost, personal sensors have potential to reduce exposure measurement error in epidemiological studies and provide valid data for citizen science studies.